Klein-Gordon particles in Godel-type Som-Raychaudhuri cosmic string spacetime and the phenomenon of spacetime associated degeneracies - Mustafa, Omar (Iop Publishing Ltd, 2023)
We argue that only exact, comprehensive, and explicit solutions for the fundamental quantum mechanical models (i.e., the Klein-Gordon (KG) oscillators and the KG-Coulomb) would help to understand and describe the effects of gravitational fields on the dynamics of such systems. In the current methodical proposal, the effects of the gravitational fields generated by a Godel-type Som-Raychaudhuri (SR) cosmic string spacetime on KG-oscillators (KG-particles in general) are studied and reported. In so doing, we revisit the KG-oscillators in a topologically trivial Godel-type spacetime background and use textbook procedures to report its exact solution that covers even and odd parities. Next, we discuss the drawbacks associated with the power series expansion approach that implies the biconfluent Heun functions/polynomials solution. We, therefore, recollect the so called pseudo perturbative shifted l expansion technique (PSLET) as an alternative and more sophisticated method/technique. Illustrative examples are used: (i) a KG-oscillator in a topologically trivial Godel-type spacetime, (ii) a quasi-free KG-oscillator in Godel SR-type cosmic string spacetime, (iii) a KG-Coulombic particle in Godel SR-type cosmic string spacetime at zero vorticity, and (iv) a massless KG-particle in Godel SR-type cosmic string spacetime in a Cornell-type Lorentz scalar potential. The corresponding exact energies are obtained from the zeroth (leading) order correction of PSLET, where all higher order correction identically vanish. The comprehensive exactness of the reported solutions manifestly suggest degeneracies associated with spacetime (STAD) phenomenon.
Keywords: Klein-Gordon (KG) particles; Godel-type Som-Raychaudhuri cosmic string spacetime; spacetime associated degeneracies